Trajectories of clinical and laboratory characteristics associated with COVID‐19 in hemodialysis patients by survival. Issue 1 (10th August 2021) - Chaudhuri, Sheetal; Lasky, Rachel; Jiao, Yue; Larkin, John; Monaghan, Caitlin; Winter, Anke; Neri, Luca; Kotanko, Peter; Hymes, Jeffrey; Lee, Sangho; Wang, Yuedong; Kooman, Jeroen P.; et al.
Abstract: Introduction: The clinical impact of COVID‐19 has not been established in the dialysis population. We evaluated the trajectories of clinical and laboratory parameters in hemodialysis (HD) patients. Methods: We used data from adult HD patients treated at an integrated kidney disease company who received a reverse transcription polymerase chain reaction (RT‐PCR) test to investigate suspicion of a severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection between May 1 and September 1, 2020. Nonparametric smoothing splines were used to fit data for individual trajectories and estimate the mean change over time in patients testing positive or negative for SARS‐CoV‐2 and those who survived or died within 30 days of first suspicion or positive test date. For each clinical parameter of interest, the difference in average daily changes between COVID‐19 positive versus negative group and COVID‐19 survivor versus nonsurvivor group was estimated by fitting a linear mixed effects model based on measurements in the 14 days before (i.e., Day −14 to Day 0) Day 0. Results: There were 12, 836 HD patients with a suspicion of COVID‐19 who received RT‐PCR testing (8895 SARS‐CoV‐2 positive). We observed significantly different trends ( p < 0.05) in pre‐HD systolic blood pressure (SBP), pre‐HD pulse rate, body temperature, ferritin, neutrophils, lymphocytes, albumin, and interdialytic weight gain (IDWG) between COVID‐19 positive and negative patients. For COVID‐19 positive group, we observed significantly different clinical trends ( p < 0.05) in pre‐HD pulse rate, lymphocytes, neutrophils, and albumin between survivors and nonsurvivors. We also observed that, in the group of survivors, most clinical parameters returned to pre‐COVID‐19 levels within 60–90 days. Conclusion: We observed unique temporal trends in various clinical and laboratory parameters among HD patients who tested positive versus negative for SARS‐CoV‐2 infection and those who survived the infection versus those who died. These trends can help to define the physiological disturbances that characterize the onset and course of COVID‐19 in HD patients.